Reward Package Design: How are multinational corporations weathering the storm? - Dickmann, Michael; Hughes, Heather (International HR Adviser, 2016)
Working abroad is about going outside of your comfort zone, accepting challenges, growing personally and professionally and, in the case of internationally assigned employees, showing exceptional commitment to an employer.